Peningkatan Kemampuan Kognitif Siswa Kelas V pada Muatan IPA Materi Ekosistem Melalui Penerapan Media Mystery Box Berbantuan Video Animasi - Deswanda, Febrina; Satriyani, Febrianti Yuli (BASICA Journal of Arts and Science in Primary Education, 2023)
Natural Science Cognitive Understanding is an ability to learn new skills and concepts, skills to understand what is happening in their environment, as well as skills to use memory and solve simple problems. This study aims to find out whether this Mystery Box media can help improve cognitive abilities in Natural Sciences material ecosystem in class V C students at SDN Aren Jaya 01 Bekasi. The research strategy used in this research is the classroom action research (CAR) design from Kemmis and Taggart. The results of the study were that the use of Mystery Box media could increase students' cognitive understanding of science in the Science subject Ecosystem Theme 5 Sub-theme 1. It was known from the results of the written test in cycle I of 59%, increasing 32% to 91% in cycle II. And the number of students who have completed the KKM is more than 75% in accordance with the specified success criteria, namely 91% or as many as 29 students out of 32 students who have completed the KKM.